Coupling tumor necrosis factor‐related apoptosis‐inducing ligand to iron oxide nanoparticles increases its apoptotic activity on HCT116 and HepG2 malignant cells: effect of magnetic core size. Issue 1 (17th April 2019) - Belkahla, Hanene; Haque, Amranul; Revzin, Alexander; Gharbi, Tijani; Constantinescu, Andrei Alexandru; Micheau, Olivier; Hémadi, Miryana; Ammar, Souad
Abstract: Tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) has been considered as a potential anticancer agent owing to its selectivity for malignant cells. However, its clinical use remains limited because of its poor efficacy. Attempts to increase its antitumor activity include, among others, its functionalization by nanoparticles (NPs). In the present study, TRAIL was grafted onto magnetic spinel iron oxide NPs of defined core size, 10 and 100 nm on average, to see whether the size of the resulting nanovectors, NV10 and NV100, respectively, might affect TRAIL efficacy and selectivity. Apoptosis induced by NV10 and NV100 was higher than by TRAIL alone in both HCT116 and HepG2 cells. At equimolar concentrations, neither the nanovectors nor the corresponding NPs displayed cytotoxicity towards normal primary hepatocytes or TRAIL receptor‐deficient HCT116 cells. NV100 exhibited superior proapoptotic activity than NV10, as evidenced by methylene blue and annexin V staining. Consistently, both caspase activation and TRAIL death‐induced signaling complex formation, as assessed by immunoblot analysis, were found to be increased in cells treated with NV100 as compared with NV10 or TRAIL alone. These results suggest that the size of NPs is important when TRAIL is vectorized for cancer therapy. Abstract : The antitumoral activity of TRAIL proapoptotic protein has been increased in cellulo by its attachment to 10‐ and 100‐nm‐sized magnetic iron oxide nanoparticles. Interestingly, this activity increases when the magnetic core size increases, opening really potentialities towards cancer nanotherapy, regarding the hyperthermia capabilities of the engineered nanohybrids.